PO 136 - FEAR-FREE ANESTHESIA FOR MITOCHONDRIAL DISEASE: FROM MAJOR ABDOMINAL TO AMBULATORY SURGERY - Neri, Inês; Freitas, Rita; Martins, Diogo; Freire, Pedro; Nascimento, Ana; Jesus, Fernanda (Revista da Sociedade Portuguesa de Anestesiologia, 2023)
x